The Relationship of Nurse Response Time in Handling Open Fracture Patients with the Risk of Hypovolemic Shock at RSUD dr. Pirngadi Medan - Youlanda Sari; Suherni Suherni (Akupun Tour Publisher, 2022)
Aid for emergency patients has a standard time of service known as response time, which is the time span of service required by nurses starting from determining triage until the completion of the process of handling emergency patients (fractures). Bleeding in small or large amounts can cause hypovolemic shock and even death. Cuts to large blood vessels in the neck, hands, and thighs can cause death in 1 – 3 minutes. While bleeding from the aorta or vena cava can cause death within 30 seconds. Emergency aid involves two main components, namely the pre-hospital phase and the hospital phase. Both components are equally important in emergency relief efforts. Emergency aid has a standard time of service known as response time, which is the time span of service required by nurses starting from determining triage to completion of the emergency handling process. This study used a quantitative research method with a descriptive correlation design. The sampling method used a total sampling method with a total sample of 26 nurses. There was a significant relationship between nurse response time in handling open fracture patients and the risk of hypovolemic shock.